DEVELOPMENT AND CHARACTERIZATION OF AMINE FUNCTIONALIZED-KIT-6/POLYSULFONE MIXED MATRIX MEMBRANES FOR CO2 AND CH4 PERMEATIONS - DING , SIE HAO (2019)
In recent years, mixed matrix membranes (MMMs) had gained popularity for CO2 and CH4 permeation and separation. However, the existence of void formation and filler agglomeration due to incompatibility of filler and polymer matrix remains as problem that reduced CO2 and CH4 gas permeation performance. Therefore, it is essential to search for suitable filler or the filler functionalization methods in order to improve the compatibility between the filler and the polymer matrix. In current work, KIT-6 and amine-functionalized KIT-6 (NH2KIT-6) were incorporated into polysulfone (PSF) polymer matrix with the aim to reduce voids formation and filler agglomeration in MMMs. The developed MMMs were subjected for CO2 and CH4 gas permeation.